Dampak Ukuran Perusahaan, Beta, dan Peringkat ESG terhadap Efisiensi Perusahaan Kelapa Sawit yang Terdaftar di IDX Selama Periode Krisis - Pritasari Wybawa, Erika; Yuliansyah, M. Roby (Pusat Penelitian Kelapa Sawit, 2026)
The palm oil industry proves to be a resilient sub-sector of agriculture, particularly during the COVID-19 crisis, contributing significantly to Indonesia's national GDP and supporting financial recovery in the post-pandemic period. This research examines the influence of company size, Beta (stock volatility), and ESG ratings on the efficiency scores of palm oil companies. A total of 20 entities listed on the Indonesia Stock Exchange (IDX) are analyzed over a 5-year period (2019–2023), including 9 ESG-rated companies. A DEA double bootstrap with left-truncated linear regression at 1 is employed to estimate the model. The results show that company size does not significantly affect efficiency, while Beta negatively impacts efficiency, indicating that higher volatility reduces performance. ESG-rated companies consistently outperform non-rated counterparts, demonstrating the positive effects of sustainable practices. This study provides a novel contribution, as no previous research explores these variables in Indonesia's palm oil industry. The findings offer valuable insights for industry practitioners and policymakers, emphasizing the importance of ESG integration for improved efficiency and sustainable growth, and supporting the formulation of policies to enhance the sector's resilience in future crises.